Nanofiber composite air purifying filter material and method for manufacturing the same
Patent Information
- Application Number
- JP2026525519
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2024-03-12
- Filing Date
- 2025-03-11
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-03-11
AI Technical Summary
【0034】 従来技術と比べて、本願は、以下の有益な効果を有する。
Smart Images

Figure 0007943727000001
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of air purification, specifically to the field of filter media for air purification, and in particular relates to a nanofiber composite air purification filter medium and a manufacturing method thereof. BACKGROUND ART
[0002] In recent years, with the rapid development of industry, the air quality problem in our country has become increasingly serious. In particular, environmental problems characterized by pollutants such as PM10 and PM2.5 have attracted increasing public attention. These particulate pollutants not only reduce air visibility, but also have a serious impact on people's health. At the same time, in indoor environments where some people carry out activities, the air may be filled with substances such as particulate matter, formaldehyde, volatile organic compounds, bacteria and pathogenic bacteria, which may similarly pose hazards to people's physical health. In order to purify air more effectively, air purification technology has attracted wide public interest, and the development of air purification filter media, which play a core role in air purification, has become a research focus among scientific researchers in recent years.
[0003] Currently, air purifying filter media such as masks are primarily composed of multilayer nonwoven fabrics, but these suffer from high resistance, low precision, and reduced filtration efficiency. Unlike nonwoven fabrics, nanofiber membrane materials have advantages such as small pore size, high porosity, and adjustable structure. However, nanofiber membrane air filtration materials have disadvantages such as a fragile structure, low stability, and high cost. Therefore, it is particularly important to manufacture new air purifying filter media by combining high-strength, dimensionally stable nonwoven fabrics with nanofiber membrane layers with high porosity. However, conventional technologies have several challenges that need to be addressed. For example, bonding nanofiber membrane layers to nonwoven fabrics is difficult, resulting in insufficient air permeability of the air purifying filter media. The main components of nonwoven fabric materials are often polymer materials such as PET and PP, which are prone to yellowing and degradation when exposed to radiation such as ultraviolet light for extended periods. Since nonwoven fabrics and nanofiber membrane materials themselves do not have bactericidal properties, their filtration against airborne bacteria and other substances is insufficient. Furthermore, prolonged use of air purifying filter media can lead to the accumulation of bacteria and other microorganisms on its surface, potentially causing secondary infections.
[0004] Patent CN115897293A discloses an antimicrobial air filtration material and a method for manufacturing the same. This application improves the strength of the filter material itself and provides high antimicrobial performance by supporting an antimicrobial substance on the fibers themselves. However, it does not address the issue of radiation protection of the air filtration material. Patent CN111203116A discloses a washable wide air filtration composite membrane, a method for manufacturing the same, and its applications. This application bonds a support material and a heavy ion microporous membrane material via ultrasonic bonding, giving the air filtration material good composite mechanical strength and air permeability. However, it does not solve the problem of low radiation protection and antimicrobial properties of the air filtration material.
[0005] Therefore, there is a strong market demand for air purification filter materials that possess good breathability, radiation protection, and antibacterial properties. [Overview of the project] [Problems that the invention aims to solve]
[0006] In response to the problems of conventional technology, this invention manufactures a nanofiber composite air purifying filter material by bonding a four-layer structure consisting of a nonwoven fabric, a nanofiber film layer, a modified meltblown nonwoven fabric, and a spunbond nonwoven fabric from top to bottom using ultrasonic bonding, thereby providing the air purifying filter material with advantages such as breathability, radiation protection, and antibacterial properties. [Means for solving the problem]
[0007] To achieve the above objectives, the technical solutions employed in this application are as follows:
[0008] A nanofiber composite air purifying filter material provided in one aspect of the present application includes a composite structure consisting of four layers, in order from top to bottom: a nonwoven fabric, a nanofiber membrane layer, a modified meltblown nonwoven fabric, and a spunbond nonwoven fabric. The aforementioned nonwoven fabric is a PET needle-punched nonwoven fabric. The raw materials for producing the nanofiber film layer, by weight, consist of 10-20 parts polylactic acid, 3-5 parts reinforcing agent, 2-4 parts modified nanoparticles, and 100-150 parts solvent. The material of the spunbond nonwoven fabric is PET or PP.
[0009] The inventors manufacture an air purification filter material by bonding a multilayer nonwoven fabric and a nanofiber membrane layer using ultrasonic bonding. Furthermore, by using PET needle-punched nonwoven fabric as the upper layer structure, the inventors give the air purification filter material robustness, durability, and low cost. Additionally, by using nonwoven fabrics manufactured using two different processes, melt-blown and spunbond, as the lower layer structure, the filter material combines the advantages of the high strength and excellent dimensional stability of the long-fiber web of spunbond nonwoven fabric with the advantages of the high bulkiness and excellent breathability of the ultra-short-fiber web of melt-blown nonwoven fabric. Meanwhile, the inventors manufacture a nanofiber membrane layer primarily made of polylactic acid as the intermediate layer. Polylactic acid has good biocompatibility and bonds well with the multilayer nonwoven fabric structure through ultrasonic bonding, thereby enhancing the adsorption capacity of the air purification filter material to nano-sized harmful particles.
[0010] In some embodiments of the present application, the polylactic acid in the nanofiber film layer is poly-L-lactic acid, The aforementioned reinforcing agent is a β-crystal nucleating agent.
[0011] Preferably, the molecular weight of the poly-L-lactic acid is 90,000 to 110,000. The aforementioned β-nucleating agent is a rare earth β-nucleating agent.
[0012] More preferably, the catalog number of the rare earth β-crystal nucleating agent is WBG-II.
[0013] This application does not particularly limit the source of the WBG-II, and includes, but is not limited to, commercially available WBG-II purchased from Guangdong Linna Functional Materials Co., Ltd., China.
[0014] Polylactic acid is an excellent biodegradable material with advantages such as being environmentally friendly, breathable, lightweight, highly resilient, and glossy. The inventors used poly-L-lactic acid, which has a wide range of raw material sources and excellent mechanical properties and moldability, and employed a rare earth β-crystal nucleating agent as the nucleating agent for polylactic acid. This overcomes the problems of polylactic acid's poor impact performance and low heat distortion temperature.
[0015] In some embodiments of the present application, the method for producing the modified nanoparticles is as follows: Step 1 involves adding TiO2 powder to a sodium hydroxide solution, sonicating it, then placing it in a polytetrafluoroethylene reaction vessel, sealing it, drying, washing, heat-drying, and grinding it to obtain a precursor. Step 2 involves taking the precursor from Step 1, adding barium nitrate and deionized water, sonicating it, then placing it in a polytetrafluoroethylene reaction vessel, sealing it, heating, washing, heat drying, and grinding to obtain nanoparticles. Step 3 includes adding 1-(3-aminopropyl)imidazole, tea polyphenol, isopropyl alcohol, and deionized water in order to the nanoparticles obtained in Step 2, followed by heating, stirring, heat drying, and pulverization to obtain modified nanoparticles.
[0016] Preferably, the method for producing the modified nanoparticles is: Step 1 involves adding TiO2 powder to a sodium hydroxide solution, sonicating it for 20-40 minutes, sealing it in a polytetrafluoroethylene reaction vessel, drying it at 200°C for 12 hours, washing it three times each with anhydrous ethanol and deionized water, heating and drying it at 60°C for 4 hours, and then grinding it to obtain a precursor. Step 2 involves taking the precursor from Step 1, adding barium nitrate and deionized water, sonicating for 30 minutes, sealing it in a polytetrafluoroethylene reaction vessel, heating at 200°C for 10 hours, washing three times each with anhydrous ethanol and deionized water, heating and drying at 60°C for 4 hours, and grinding to obtain nanoparticles. Step 3 includes adding 1-(3-aminopropyl)imidazole, tea polyphenol, isopropyl alcohol, and deionized water in order to the nanoparticles obtained in Step 2, heating at 40-50°C, stirring for 20-40 minutes, heating and drying at 60°C for 4 hours, and grinding to obtain modified nanoparticles.
[0017] Here, the particle size of the TiO2 powder is 20-40 nm.
[0018] This application does not particularly limit the source of the TiO2 powder, and includes, but is not limited to, commercially available sources, including purchase from Shanghai Alading Biochemical Technology Co., Ltd., China.
[0019] In some embodiments of the present application, in step 3, the mass ratio of the nanoparticles obtained in step 2, 1-(3-aminopropyl)imidazole, and tea polyphenols is 1:(0.3~0.5):(0.15~0.35).
[0020] Preferably, in step 3, the mass ratio of the nanoparticles obtained in step 2, 1-(3-aminopropyl)imidazole, and tea polyphenols is 1:0.4:0.25.
[0021] Compared with ordinary nonwoven fabrics, nanofiber membranes have smaller pore sizes and higher filtration efficiency, and can particularly enhance the filtration efficiency of nanoparticles. Among them, polylactic acid, as an environmentally friendly biodegradable material, has advantages such as light weight, good air permeability, and excellent resilience, but has the disadvantage of insufficient strength and antibacterial properties. In order to achieve optimization of the performance of polylactic acid nanofiber membranes, the inventors produce modified nanoparticles by modifying TiO₂ powder. On the other hand, the inventors prepare highly active BaTiO₃ nanoparticles from TiO₂ powder through a two-step hydrothermal method. The BaTiO₃ nanoparticles can be embedded in situ on the surface of polylactic acid, overcoming the problem of poor dispersion of TiO₂ powder in polylactic acid, so that the antibacterial properties of the polylactic acid nanofiber membrane are better. In addition, the embedding of BaTiO₃ nanoparticles on the surface of polylactic acid improves the overall crystallinity of the nanofiber membrane, further strengthens the intermolecular interaction, and improves the strength of the polylactic acid nanofiber membrane. On the other hand, the inventors introduced 1-(3-aminopropyl)imidazole and tea polyphenols into the BaTiO₃ nanoparticles. By introducing 1-(3-aminopropyl)imidazole into polylactic acid via the BaTiO₃ nanoparticles, imidazole groups and amide groups can appear on the surface of polylactic acid. The imidazole groups can enhance the radiation protection performance of the nanofiber membrane. Since the amide groups can form hydrogen bonds with polylactic acid molecules, they accelerate the nucleation rate of polylactic acid, reduce the usage amount of the nucleating agent, and save costs. As a natural substance, tea polyphenols can enhance the radiation protection property of the nanofiber membrane layer.
[0022] In some embodiments of the present application, the solvent is polyethylene glycol or dichloromethane.
[0023] Preferably, the solvent is polyethylene glycol with a molecular weight of 400 to 600.
[0024] In some embodiments of the present application, the method for producing the nanofiber membrane layer comprises mixing polylactic acid, a reinforcing agent, and modified nanoparticles in a solvent, leaving the mixture to stand for 4 to 6 hours at 40 to 50°C, stirring to obtain a blended solution, and further performing electrospinning to obtain a nanofiber membrane layer.
[0025] In some embodiments of the present application, the method for producing the modified melt-blown nonwoven fabric comprises step (1): adding concentrated hydrochloric acid and deionized water to a reaction vessel, adding samarium oxide powder in several portions, heating to 45 to 55°C, stirring, performing suction filtration, adding aqueous ammonia to adjust the pH to 7.5 to 8.5, and further performing suction filtration, washing, filtering, and drying to obtain a first reaction product; step (2): taking the first reaction product from the step (1), adding methacrylic acid, heating to 75 to 85°C, stirring until the solution becomes transparent, filtering, performing vacuum distillation, cooling, performing suction filtration, and drying to obtain a second reaction product; step (3): mixing the second reaction product from the step (2), a polyethylene masterbatch, and a polypropylene masterbatch, drying the mixture in a vacuum environment, and then subjecting the dried mixture to extrusion and melt spinning processes to obtain composite fibers; step (4): adding ferrous sulfate, deionized water, and N-isopropylacrylamide into a reaction kettle, mixing them, adding the composite fibers from the step (3), introducing an inert gas for 8 to 15 minutes, heating at 65 to 75°C for 2 to 4 hours, washing while irradiating with ultraviolet light, and drying to obtain a mixture; and step (5): subjecting the mixture obtained in the step (4) to a melt-blowing process to obtain the modified melt-blown nonwoven fabric.
[0026] Preferably, the method for producing the modified melt-blown nonwoven fabric comprises step (1): adding concentrated hydrochloric acid and deionized water to a reaction vessel, adding samarium oxide powder in several portions, heating to 50°C, stirring for 20 to 40 minutes, performing suction filtration, adding 25 wt% aqueous ammonia to adjust the pH to 8.0, further performing suction filtration, washing three times with deionized water, filtering, and drying at 100°C for 12 hours to obtain a first reaction product; Step (2) involves taking the first reaction product from step (1), adding methacrylic acid, heating to 80°C, stirring until the solution becomes clear, filtering, vacuum distillation, cooling to room temperature, suction filtration, and drying at 100°C for 12 hours to obtain the second reaction product. Step (3) involves mixing the second reaction product from step (2), the polyethylene masterbatch, and the polypropylene masterbatch, drying them in a vacuum environment at 100°C for 12 hours, and then obtaining composite fibers through an extrusion and melt spinning process. Step (4) involves placing ferrous sulfate, deionized water, and N-isopropylacrylamide in a reaction vessel, mixing them, adding the composite fibers from step (3), passing nitrogen gas through for 10 minutes, heating at 70°C for 3 hours, washing three times with deionized water while irradiating with ultraviolet light at 220-260 nm, and drying at 60°C for 4 hours to obtain the mixture. The process includes step (5) of performing a melt-blowing process on the mixture obtained in step (4) to obtain a modified melt-blown nonwoven fabric.
[0027] Of these, the molecular weight of polyethylene masterbatch is 80,000 to 100,000, and the molecular weight of polypropylene masterbatch is 100,000 to 110,000.
[0028] In some embodiments of the present application, in step (3), the mass ratio of the second reaction product in step (2), polyethylene masterbatch and polypropylene masterbatch is 1:(3~5):(7~9), In step (4), the mass ratio of the composite fiber from step (3) to N-isopropylacrylamide is 1:(0.15~0.25).
[0029] Preferably, in step (3), the mass ratio of the second reaction product in step (2), polyethylene masterbatch and polypropylene masterbatch is 1:4:8. In step (4), the mass ratio of the composite fiber from step (3) to N-isopropylacrylamide is 1:0.2.
[0030] This application does not particularly limit the source of the polyethylene masterbatch, and includes, but is not limited to, commercially available products, including purchase from Dongguan Yili Plastic Co., Ltd., China. This application also does not particularly limit the source of the polypropylene masterbatch, and includes, but is not limited to, commercially available products, including purchase from Shenzhen Jin Da Quan Technology Co., Ltd., China.
[0031] Meltblown nonwoven fabrics are a type of nonwoven fabric manufactured from polymer materials through a meltblown process. Among these, two-component meltblown nonwoven fabrics are attracting attention because they can compensate for the shortcomings of single polymer properties. The inventors have manufactured two-component meltblown nonwoven fabrics using polyethylene masterbatch and polypropylene masterbatch as the main components. Polypropylene has advantages such as flame retardancy and high temperature resistance, but it has low breathability and low radiation resistance. Compared to polypropylene, polyethylene has a dispersed and loose molecular chain structure, resulting in excellent breathability, comfort, and softness. Furthermore, when polyethylene absorbs radiation, it undergoes a photocrosslinking reaction within its structure, thereby improving the radiation protection of the meltblown nonwoven fabric. In addition, polyethylene utilizes its hydrophobicity to prevent water droplets from remaining on the surface of the nonwoven fabric, achieving an anti-fogging effect. The inventors have also added samarium oxide powder, which has radiation protection properties, to the meltblown nonwoven fabric, and have prepared samarium methacrylate by modifying the samarium oxide powder. The unsaturated reactive groups in samarium methacrylate can readily undergo in-situ compatibility reactions with polypropylene, resulting in a stronger bond between the samarium oxide powder and the meltblown nonwoven fabric, which is advantageous for improving the radiation protection performance of the air purification filter material. On the other hand, the inventors introduced temperature-sensitive N-isopropylacrylamide into the composite fibers. N-isopropylacrylamide can change from hydrophilic to hydrophobic as the reaction temperature increases, effectively filtering small molecular oil droplets from the nonwoven fabric surface. The reaction between the amide bond and the acrylic acid bond of samarium methacrylate promotes the grafting of N-isopropylacrylamide in the composite fibers. In addition, the ferrous ions in ferrous sulfate provide a certain antioxidant effect during the synthesis process of the meltblown nonwoven fabric, thereby further enhancing the radiation protection performance of the air purification filter material.
[0032] In another aspect of the present application, a method for manufacturing a nanofiber composite air purifying filter material described in the above technical solution is provided. This method is Step S1 involves laminating four layers of materials—nonwoven fabric, nanofiber film layer, modified meltblown nonwoven fabric, and spunbond nonwoven fabric—in order from top to bottom. The process includes step S2, which involves bonding and shaping the four layers of material stacked in step S1 by ultrasonic bonding to obtain a nanofiber composite air purifying filter material.
[0033] In some embodiments of the present application, the output of the ultrasonic bonding is 400 to 600 kW. The ultrasonic frequency is 90-110 Hz.
[0034] Compared to the prior art, this invention has the following beneficial effects.
[0035] (1) The present invention provides a nanofiber composite air purifying filter material with breathability, radiation protection, and antibacterial properties, by bonding a four-layer structure of nonwoven fabric, nanofiber film layer, modified meltblown nonwoven fabric, and spunbond nonwoven fabric from top to bottom using ultrasonic bonding.
[0036] (2) The present invention provides a nanofiber film layer that has high strength, antibacterial properties and radiation protection properties, by manufacturing a nanofiber film layer mainly composed of polylactic acid, with the addition of a reinforcing agent, modified nanoparticles and a solvent.
[0037] (3) The present invention provides a modified meltblown nonwoven fabric by using polypropylene and polyethylene masterbatch as the main polymer components of a two-component meltblown nonwoven fabric, and adding samarium oxide powder which has radiation shielding properties and N-isopropylacrylamide which has temperature sensitivity, thereby providing a modified meltblown nonwoven fabric that has good breathability, radiation shielding properties and anti-fogging properties.
[0038] (4) The air purifying filter material manufactured according to this application has excellent air permeability, radiation protection, and antibacterial properties, and can be widely used in the field of air purifying filter materials, and has high commercial application value. [Modes for carrying out the invention]
[0039] The present application will be described below with reference to specific embodiments. The following embodiments are illustrative and intended solely to illustrate the present application, and are not intended to limit it. Other combinations and various improvements within the concept of the present application can be made without departing from the gist or scope of the present application.
[0040] In the following examples, with the exception of the modified nanoparticles and modified meltblown nonwoven fabric, all remaining compound monomers and related reagents used are commercially available. Of these, the PET needle-punched nonwoven fabric and PET spunbond nonwoven fabric were purchased from Jiangxi Haorui Industrial Materials Co., Ltd., China. The polylactic acid is poly-L-lactic acid with an average molecular weight of 100,000, the reinforcing agent is a rare-earth β-crystal nucleating agent with the catalog number WBG-II, purchased from Guangdong Linna Functional Materials Co., Ltd., China. The average particle size of the TiO2 powder is 30 nm, purchased from Shanghai Alading Biochemical Technology Co., Ltd., China. The average molecular weight of the polyethylene masterbatch is 90,000, purchased from Dongguan Yili Plastic Co., Ltd., China. The average molecular weight of the polypropylene masterbatch is 105,000, purchased from Shenzhen Jin Daquan Technology Co., Ltd., China. Polyethylene glycol was purchased from Tianjin Daixu Chemical Trading Co., Ltd., China, with molecular weights of 400, 500, and 600.
[0041] [Manufacturing Example 1] The method for synthesizing modified nanoparticle A is: Step 1 involves adding 30 g of TiO2 powder to 100 ml of 8 mol / L sodium hydroxide solution, sonicating for 30 minutes, sealing the mixture in a polytetrafluoroethylene reaction vessel, drying at 200°C for 12 hours, washing three times each with anhydrous ethanol and deionized water, heating and drying at 60°C for 4 hours, and grinding to obtain a precursor. Step 2 involves taking 10g of the precursor from Step 1, adding 22g of barium nitrate and 50ml of deionized water, sonicating for 30 minutes, sealing it in a polytetrafluoroethylene reaction vessel, heating at 200°C for 10 hours, washing three times each with anhydrous ethanol and deionized water, heating and drying at 60°C for 4 hours, and grinding to obtain nanoparticles. Step 3 includes adding 8 g of 1-(3-aminopropyl)imidazole, 5 g of tea polyphenol, 15 ml of isopropyl alcohol, and 40 ml of deionized water to 20 g of nanoparticles obtained in Step 2, heating at 45°C, stirring for 30 minutes, heating and drying at 60°C for 4 hours, and grinding to obtain modified nanoparticles A.
[0042] [Manufacturing Example 2] The synthesis method for modified nanoparticles B is the same as that for modified nanoparticles A, and the raw materials used and their respective content are substantially the same as those for modified nanoparticles A, differing only in that in step 3, the masses of 1-(3-aminopropyl)imidazole and tea polyphenols are changed to 5 g and 2.4 g, respectively.
[0043] [Manufacturing Example 3] The method for synthesizing modified meltblown nonwoven fabric A is: Step (1) involves adding 50 ml of 38 wt% concentrated hydrochloric acid and 100 ml of deionized water to a reaction vessel, adding 30 g of samarium oxide powder in several batches, heating to 50°C, stirring for 30 minutes, suction filtration, adding 25 wt% aqueous ammonia to adjust the pH to 8.0, suction filtration again, washing three times with deionized water, filtration, and drying at 100°C for 12 hours to obtain the first reaction product. Step (2) involves taking 20 g of the first reaction product from step (1), adding 40 g of methacrylic acid, heating to 80°C, stirring until the solution becomes clear, filtering, performing vacuum distillation, cooling to room temperature, suction filtering, and drying at 100°C for 12 hours to obtain the second reaction product. Step (3) involves mixing 10 g of the second reaction product from step (2), 40 g of polyethylene masterbatch, and 80 g of polypropylene masterbatch, drying them in a vacuum environment at 100°C for 12 hours, and then obtaining composite fibers through extrusion and melt spinning processes. Step (4) involves placing 10g of ferrous sulfate, 100ml of deionized water, and 8g of N-isopropylacrylamide into a reaction vessel, mixing, adding 40g of the composite fiber from step (3), passing nitrogen gas through for 10 minutes, heating at 70°C for 3 hours, washing three times with deionized water while irradiating with 240nm ultraviolet light, and drying at 60°C for 4 hours to obtain the mixture. The process includes step (5) of performing a melt-blowing process on the mixture obtained in step (4) to obtain a modified melt-blown nonwoven fabric A.
[0044] [Manufacturing Example 4] The synthesis method for modified meltblown nonwoven fabric B is the same as that for modified meltblown nonwoven fabric A, and the raw materials used and their respective content are substantially the same as those for modified meltblown nonwoven fabric A, differing only in that in step (3), the masses of the polyethylene masterbatch and the polypropylene masterbatch are changed to 25g and 65g, respectively.
[0045] [Manufacturing Example 5] The synthesis method for modified meltblown nonwoven fabric C is the same as that for modified meltblown nonwoven fabric A, and the raw materials used and their respective content are substantially the same as those for modified meltblown nonwoven fabric A, differing only in that the mass of N-isopropylacrylamide is changed to 4.5 g in step (4).
[0046] Example 1 The nanofiber composite air purifying filter material has a composite structure consisting of four layers, from top to bottom: a nonwoven fabric, a nanofiber membrane layer, a modified meltblown nonwoven fabric A, and a spunbond nonwoven fabric. Here, the thicknesses of the nonwoven fabric, nanofiber film layer, modified meltblown nonwoven fabric A, and spunbond nonwoven fabric are 50 μm, 0.3 μm, 40 μm, and 20 μm, respectively.
[0047] The aforementioned nonwoven fabric is a PET needle-punched nonwoven fabric. The nanofiber film layer comprises, by weight, 15 parts polylactic acid, 4 parts reinforcing agent, 3 parts modified nanoparticles A, and 125 parts solvent as raw materials.
[0048] The material of the aforementioned spunbond nonwoven fabric is PET spunbond nonwoven fabric. Here, the solvent is polyethylene glycol with a molecular weight of 500.
[0049] The method for manufacturing the nanofiber film layer is as follows: The process includes the steps of mixing polylactic acid, a reinforcing agent, and modified nanoparticles in a solvent, allowing the mixture to stand for 5 hours under conditions of 45°C, stirring to obtain a blended solution, and then electrospinning to obtain a nanofiber film layer.
[0050] The method for manufacturing the nanofiber composite air purifying filter material in this embodiment is: Step S1 involves laminating four layers of materials—nonwoven fabric, nanofiber film layer, modified meltblown nonwoven fabric A, and spunbond nonwoven fabric—in order from top to bottom. The process includes step S2, in which the four layers of material stacked in step S1 are bonded and molded by ultrasonic bonding to obtain a nanofiber composite air purifying filter material.
[0051] Here, the output power of the ultrasonic bonding is 500 kW, and the ultrasonic frequency is 100 Hz.
[0052] Example 2 The nanofiber composite air purifying filter material has a composite structure consisting of four layers, from top to bottom: a nonwoven fabric, a nanofiber membrane layer, a modified meltblown nonwoven fabric A, and a spunbond nonwoven fabric. Here, the thicknesses of the nonwoven fabric, nanofiber film layer, modified meltblown nonwoven fabric A, and spunbond nonwoven fabric are the same as in Example 1.
[0053] The aforementioned nonwoven fabric is a PET needle-punched nonwoven fabric. The nanofiber film layer comprises, by weight, 10 parts polylactic acid, 3 parts reinforcing agent, 3 parts modified nanoparticles A, and 100 parts solvent as raw materials.
[0054] The material of the aforementioned spunbond nonwoven fabric is PET spunbond nonwoven fabric. Here, the solvent is polyethylene glycol with a molecular weight of 400.
[0055] The method for manufacturing the nanofiber film layer is as follows: The process includes the steps of mixing polylactic acid, a reinforcing agent, and modified nanoparticles in a solvent, allowing the mixture to stand for 4 hours at 40°C, stirring to obtain a blended solution, and then electrospinning to obtain a nanofiber film layer.
[0056] The method for manufacturing the nanofiber composite air purifying filter material in this embodiment is: Step S1 involves laminating four layers of materials—nonwoven fabric, nanofiber film layer, modified meltblown nonwoven fabric A, and spunbond nonwoven fabric—in order from top to bottom. The process includes step S2, in which the four layers of material stacked in step S1 are bonded and molded by ultrasonic bonding to obtain a nanofiber composite air purifying filter material.
[0057] Here, the output power of the ultrasonic bonding is 400kW, and the ultrasonic frequency is 90Hz.
[0058] Example 3 The nanofiber composite air purifying filter material has a composite structure consisting of four layers, from top to bottom: a nonwoven fabric, a nanofiber membrane layer, a modified meltblown nonwoven fabric A, and a spunbond nonwoven fabric. Here, the thicknesses of the nonwoven fabric, nanofiber film layer, modified meltblown nonwoven fabric A, and spunbond nonwoven fabric are the same as in Example 1.
[0059] The aforementioned nonwoven fabric is a PET needle-punched nonwoven fabric. The nanofiber film layer comprises, by weight, 20 parts polylactic acid, 5 parts reinforcing agent, 3 parts modified nanoparticles A, and 150 parts solvent as raw materials.
[0060] The material of the aforementioned spunbond nonwoven fabric is PET spunbond nonwoven fabric. Here, the solvent is polyethylene glycol with a molecular weight of 600.
[0061] The method for manufacturing the nanofiber film layer is as follows: The process includes the steps of mixing polylactic acid, a reinforcing agent, and modified nanoparticles in a solvent, allowing the mixture to stand for 6 hours under conditions of 50°C, stirring to obtain a blended solution, and then electrospinning to obtain a nanofiber film layer.
[0062] The method for manufacturing the nanofiber composite air purifying filter material in this embodiment is: Step S1 involves laminating four layers of materials—nonwoven fabric, nanofiber film layer, modified meltblown nonwoven fabric A, and spunbond nonwoven fabric—in order from top to bottom. The process includes step S2, which involves bonding and shaping the four layers of material stacked in step S1 by ultrasonic bonding to obtain a nanofiber composite air purifying filter material.
[0063] Here, the output power of the ultrasonic bonding is 600 kW, and the ultrasonic frequency is 110 Hz.
[0064] Example 4 The nanofiber composite air purifying filter material has a composite structure consisting of four layers, from top to bottom: a nonwoven fabric, a nanofiber membrane layer, a modified meltblown nonwoven fabric A, and a spunbond nonwoven fabric. Here, the thicknesses of the nonwoven fabric, nanofiber film layer, modified meltblown nonwoven fabric A, and spunbond nonwoven fabric are the same as in Example 1.
[0065] The aforementioned nonwoven fabric is a PET needle-punched nonwoven fabric. The nanofiber film layer comprises, by weight, 12 parts polylactic acid, 3.5 parts reinforcing agent, 2 parts modified nanoparticles A, and 120 parts solvent as raw materials.
[0066] The material of the aforementioned spunbond nonwoven fabric is PET spunbond nonwoven fabric. Here, the solvent is polyethylene glycol with a molecular weight of 500.
[0067] The method for manufacturing the nanofiber film layer and the nanofiber composite air purifying filter material in this embodiment is the same as in Example 1.
[0068] Example 5 The nanofiber composite air purifying filter material has a composite structure consisting of four layers, from top to bottom: a nonwoven fabric, a nanofiber membrane layer, a modified meltblown nonwoven fabric A, and a spunbond nonwoven fabric. Here, the thicknesses of the nonwoven fabric, nanofiber film layer, modified meltblown nonwoven fabric A, and spunbond nonwoven fabric are the same as in Example 1.
[0069] The aforementioned nonwoven fabric is a PET needle-punched nonwoven fabric. The nanofiber film layer comprises, by weight, 18 parts polylactic acid, 4.5 parts reinforcing agent, 4 parts modified nanoparticles A, and 140 parts solvent as raw materials.
[0070] The material of the aforementioned spunbond nonwoven fabric is PET spunbond nonwoven fabric. Here, the solvent is polyethylene glycol with a molecular weight of 500.
[0071] The method for manufacturing the nanofiber film layer and the nanofiber composite air purifying filter material in this embodiment is the same as in Example 1.
[0072] Example 6 According to this application, a nanofiber composite air purifying filter material and a method for manufacturing the same are provided. The specific embodiment is the same as in Example 1, differing in that modified nanoparticles A are replaced with the same amount of modified nanoparticles B.
[0073] Example 7 According to the present application, a nanofiber composite air purifying filter material and a method for manufacturing the same are provided. The specific embodiment is the same as in Example 1, differing in that modified meltblown nonwoven fabric A is replaced with the same amount of modified meltblown nonwoven fabric B.
[0074] Example 8 According to the present application, a nanofiber composite air purifying filter material and a method for manufacturing the same are provided. The specific embodiment is the same as in Example 1, differing in that modified meltblown nonwoven fabric A is replaced with the same amount of modified meltblown nonwoven fabric C.
[0075] Comparative Example 1 This comparative example provides a nanofiber composite air purifying filter material and a method for manufacturing the same. The specific embodiment is the same as in Example 1, differing in that modified nanoparticles A are replaced with TiO2 powder.
[0076] Comparative Example 2 This comparative example provides a nanofiber composite air purifying filter material and a method for manufacturing the same. The specific embodiment is the same as in Example 1, differing in that the modified meltblown nonwoven fabric A is replaced with a conventional commercially available polypropylene meltblown nonwoven fabric.
[0077] The conventional polypropylene meltblown nonwoven fabric used in this comparative example was purchased from Jiangxi Haorui Industrial Materials Co., Ltd., China.
[0078] Performance testing The air permeability, radiation protection, and antibacterial properties of the nanofiber composite air purifying filter media of Examples 1-8 and Comparative Examples 1-2 were tested, and the test results are shown in Table 1.
[0079] (1) Breathability Air permeability is determined by testing the filtration efficiency (dust-proof rate) of the air purification filter material, based on the GB 2626-2006 standard.
[0080] (2) Radiation protection Radiation protection is determined by testing the degree of yellowing. After irradiating the test specimen with a carbon arc lamp type sunshine weather meter for 30 hours, the degree of yellowing of the test specimen is measured with a colorimeter and expressed as a yellowing value (YI).
[0081] (3) Antibacterial properties Referring to standard QB / T4371-2012, antimicrobial performance is determined by the sterilization rate. A sterilization rate of 90% or higher indicates that the sample has antimicrobial effects, and a sterilization rate of 99% or higher indicates that the sample has excellent antimicrobial effects. [Table 1]
[0082] As can be seen from the data in Table 1, the air purifying filter media in Examples 1 to 5 of this application have high air permeability, radiation protection, and antibacterial properties. In Example 6, the ratio of the main components in the modified nanoparticles was changed so that 1-(3-aminopropyl)imidazole and tea polyphenols could not react sufficiently with the BaTiO3 nanoparticles. As a result, the radiation protection and antibacterial properties of the air purifying filter media were both reduced to some extent, but the air permeability was hardly affected. In Examples 7 and 8, the ratio of polyethylene masterbatch and polypropylene masterbatch in the modified meltblown nonwoven fabric, and the reaction ratio of composite fibers and N-isopropylacrylamide were changed, respectively, so that the highly permeable polyethylene could not function sufficiently. In addition, the photocrosslinking reaction after radiation absorption became insufficient, or the grafting of N-isopropylacrylamide and composite fibers became insufficient. All of these significantly reduced the air permeability and radiation protection of the air purifying filter media, but did not affect the antibacterial properties. Comparative Examples 1 and 2 used TiO2 powder and conventional commercially available polypropylene meltblown nonwoven fabric, respectively, instead of modified nanoparticles A and modified meltblown nonwoven fabric A. The test results showed that the permeability, radiation protection, and antibacterial properties of the manufactured air purifying filter media were all low.
[0083] The embodiments described above are for illustrative purposes only, to illustrate the technical concept and features of the present application, and are intended to enable those familiar with the art to understand and implement the contents of the present application, and are not intended to limit the scope of protection of the present application. Any equivalent modifications or alterations made based on the substance of the gist of the present application shall be included within the scope of protection of the present application.
Claims
1. The composite structure consists of four layers, from top to bottom: a nonwoven fabric, a nanofiber film layer, a modified meltblown nonwoven fabric, and a spunbond nonwoven fabric. The aforementioned nonwoven fabric is a PET needle-punched nonwoven fabric. The raw material for producing the nanofiber film layer comprises, by weight, 10 to 20 parts polylactic acid, 3 to 5 parts reinforcing agent, 2 to 4 parts modified nanoparticles, and 100 to 150 parts solvent. The material of the aforementioned spunbond nonwoven fabric is PET or PP. The modified nanoparticles are barium titanate nanoparticles having a composite modification layer of 1-(3-aminopropyl)imidazole and tea polyphenols bonded to their surface. The modified meltblown nonwoven fabric is a meltblown nonwoven fabric of polyethylene and polypropylene composite fibers containing samarium methacrylate, and poly-N-isopropylacrylamide is grafted onto the surface of the composite fibers. Nanofiber composite air purifying filter material.
2. The polylactic acid in the aforementioned nanofiber film layer is poly-L-lactic acid. The reinforcing agent is a β-crystal nucleating agent. The nanofiber composite air purifying filter material according to claim 1.
3. In the modified nanoparticles, The mass ratio of the barium titanate nanoparticles, 1-(3-aminopropyl)imidazole, and tea polyphenols is 1:(0.3-0.5):(0.15-0.35). The nanofiber composite air purifying filter material according to claim 1.
4. The solvent is polyethylene glycol. The nanofiber composite air purifying filter material according to claim 1.
5. The thickness of the aforementioned nanofiber film layer is It is 0.3 μm. The nanofiber composite air purifying filter material according to claim 1.
6. Step S1 involves laminating the four layers of materials, the nonwoven fabric, the nanofiber film layer, the modified meltblown nonwoven fabric, and the spunbond nonwoven fabric, in order from top to bottom. Step S2 involves bonding and shaping the four layers of material stacked in step S1 by ultrasonic bonding to obtain a nanofiber composite air purifying filter material. including, A method for manufacturing a nanofiber composite air purifying filter material according to any one of claims 1 to 5.
7. The output of the ultrasonic bonding is 400 to 600 kW. The ultrasonic frequency is 90-110 Hz. A method for producing a nanofiber composite air purifying filter material according to claim 6.
8. Before step S1, TiO 2 Step 1 involves adding the powder to a sodium hydroxide solution, ultrasonically treating it, then placing it in a polytetrafluoroethylene reaction vessel, sealing it, drying, washing, heat-drying, and grinding it to obtain a precursor. Step 2 involves taking the precursor from Step 1, adding barium nitrate and deionized water, sonicating it, then placing it in a polytetrafluoroethylene reaction vessel, sealing it, heating, washing, heat drying, and grinding to obtain nanoparticles. Step 3 involves sequentially adding 1-(3-aminopropyl)imidazole, tea polyphenol, isopropyl alcohol, and deionized water to the nanoparticles obtained in Step 2, followed by heating, stirring, heat drying, and pulverization to obtain modified nanoparticles. Step 4 involves mixing polylactic acid, a reinforcing agent, and the modified nanoparticles in a solvent, allowing them to stand for 4 to 6 hours under conditions of 40 to 50°C, stirring to obtain a blended solution, and then electrospinning to obtain the nanofiber film layer. including A method for producing a nanofiber composite air purifying filter material according to claim 6.
9. In step 3, the mass ratio of the nanoparticles obtained in step 2, 1-(3-aminopropyl)imidazole, and tea polyphenols is 1:(0.3-0.5):(0.15-0.35). A method for producing a nanofiber composite air purifying filter material according to claim 8.
Citation Information
Patent Citations
Novel dustproof, antibacterial and antiviral nano-fiber mask
CN111235756A
Improved filter media with nanoweb layer
JP2012512731A
Filter medium for air filter, air filter unit and method for manufacturing filter medium for air filter
JP2013063424A
Filtering material for antibacterial air filter
JP2014144420A